2022
DOI: 10.1186/s12974-022-02509-8
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 4D is upregulated in neurons of diseased brains and triggers astrocyte reactivity

Abstract: Background The close interaction and interdependence of astrocytes and neurons allows for the possibility that astrocyte dysfunction contributes to and amplifies neurodegenerative pathology. Molecular pathways that trigger reactive astrocytes may represent important targets to preserve normal homeostatic maintenance and modify disease progression. Methods Semaphorin 4D (SEMA4D) expression in the context of disease-associated neuropathology was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…Importantly, this study found that TREM2, PLXNA1, and DAP12 co-immunoprecipitate in a TREM2-dependent manner, consistent with the formation of a complex ( 30 , 31 ). Furthermore, additional studies also linked plexin-semaphorin signaling to immune activation and neurodegeneration ( 5 , 2224 , 32 ). Given this role for SEMA6D in the immune activation of myeloid cells, we aimed to test the potential role of the SEMA6D-TREM2/PLXNA1 signaling axis in AD.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, this study found that TREM2, PLXNA1, and DAP12 co-immunoprecipitate in a TREM2-dependent manner, consistent with the formation of a complex ( 30 , 31 ). Furthermore, additional studies also linked plexin-semaphorin signaling to immune activation and neurodegeneration ( 5 , 2224 , 32 ). Given this role for SEMA6D in the immune activation of myeloid cells, we aimed to test the potential role of the SEMA6D-TREM2/PLXNA1 signaling axis in AD.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, neurons express higher levels of Sema4D in Alzheimer's and Huntington's disease, and its blockade can reduce astrocyte reactivity 70 .…”
Section: Discussionmentioning
confidence: 99%
“… 5 We, therefore, investigated expression of SEMA4D and its receptors under disease conditions in neurons and astrocytes. 4 We made the following observations: SEMA4D staining of post‐mortem sections from normal human control and from people with HD and AD demonstrated significantly increased SEMA4D expression in neurons during disease progression in brain regions of three different patients at each of HD pathological stages 0, 1, and 2 as well as in advanced AD. plexin‐B1 and plexin‐B2 receptors are highly expressed on astrocytes intimately associated with neurons in brain.…”
mentioning
confidence: 89%
“…In two recent publications, 3 . 4 we investigated the signals that trigger the striking morphological transformation of astrocytes. Based on the previous work of our own and others, we were aware of the important role of the semaphorin 4D:plexin‐B1/B2 pathway in triggering collapse of the actin cytoskeleton.…”
mentioning
confidence: 99%
See 1 more Smart Citation